The Effects Of Corporate Support For Information Systems Development On The Performance Of The Accountant - NYENJE HAKEEM; NUR INDRIANTORO (Faculty of Economics and Business, Universitas Gadjah Mada, 1997)
This study, investigated the interacting effects of Management Support for Information Systems (MSIS), User Involvement in Information Systems Development (ISD) and Perceived Information Systems Benefits (PISB) on the performance of the accountant. The data on the four variables was collected through mail surveys requesting accountants employed in different organisations to participate in the study. Thirtyeight responses were returned from a cross section of Indonesian Organisations. The data was analysed using multiple regression models and partial derivative analyses of the regression models. To support the hypotheses, the coefficient of the interaction term in the regression had to be significant and positive. If the coefficient of the interaction was found positive, the corresponding incremental r2 was considered statistically significant at the same probability level. The results confirmed that, the positive effects of User Involvement in Information System Development on the accountant's performance will be higher when the level of Management Support for Information Systems is high. It also showed that Management Support for Information Systems had a positive mono-tonic effect on the performance of the accountant over the entire observed range of Perceived Information Systems Benefits and that the positive effects of User Involvement in Information Systems Development on the performance of the accountant will be higher when the level of Perceived Information Systems Benefits is high. This study,is unable to prove that, the positive effects of the combination between Management Support for Information Systems and User Involvement in Information Systems Development on the performance of the accountant will be higher when the levels of Perceived Information Systems Benefits are high. This means that any level of PISB will lead to positive effects in the performance of the accountant. This was no different from the observations made by interviewees.